The effect of accompanying anxiety and depression on patients with different vestibular syndromes - Feng, Shuai; Zang, Jian (Frontiers in Aging Neuroscience, 2023)
Objective: This study aims to investigate the situation of vertigo disorder combined with anxiety and depression in patients with different types of vestibular syndrome.Methods: 330 patients with vertigo in otolaryngology outpatient department were selected, and clinical information such as age, gender, and scores of Dizziness handicap inventory (DHI), Generalized anxiety disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9) were collected. Analyzed the differences among acute vestibular syndrome (AVS), episodic vestibular syndrome (EVS) and chronic vestibular syndrome (CVS) in terms of age, gender, comorbid anxiety and depression, and the multivariate ordered logistic regression analysis was used to evaluate the relationship between the above factors and the degree of vertigo disorder.Results: The three types of vestibular syndrome had no significant difference in age composition, sex composition, anxiety and depression. There was no significant difference in the probability of anxiety and depression among vertigo patients of different ages and genders. The total score of vertigo disorder and each sub-item score were higher in patients with anxiety and depression. Patients with anxiety mainly manifested in EVS and CVS, while patients with depression mainly manifested in EVS and AVS. The probability of increased vertigo in anxious patients was 4.65 times that of nonanxious patients, and the probability of increased vertigo in depressed patients was 3.49 times that of non-depressed patients. Age and gender had no statistically significant effect on the degree of vertigo. In patients with EVS, anxiety and depression had a significant effect on the degree of vertigo; in patients with CVS, anxiety had a significant effect on the degree of vertigo, but depression had no significant effect. Conclusion: Age and gender do not significantly affect the degree of vertigo disorder and mental state in various vestibular syndromes. Instead, anxiety and depression are the risk factors for aggravating the degree of vertigo disorder, and manifest differently in each type of vestibular syndrome. Therefore, it is necessary to use a quick scale tool to conduct a standardized screening of the psychological status of patients with vertigo.